The use of drought resistance indices in the study of the spring bread wheat collection under the conditions of Aktobe Region - Zh. T. Kalybekova; V. I. Tsygankov; E. V. Zuev; L. Yu. Novikova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Due to the global climate warming trend, the breeding of new drought-resistant cultivars of spring bread wheat remains a priority task for Western Kazakhstan breeders. However, an increase in resistance is often accompanied by a decrease in genotype productivity, and searching for an optimal combination of these characteristics is a trend in contemporary plant breeding.Materials and methods. In 2017–2019, 175 spring bread wheat accessions from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) and locally developed contemporary cultivars were studied under the conditions of Aktobe Agricultural Station. The field study was carried out according to VIR’s guidelines. To assess the drought tolerance of the accessions, the following indices were used: mean productivity (MP), stress tolerance (TOL), yield stability index (YSI), drought resistance index (DI), and stress tolerance index (STI).Results and discussion. Drought tolerance indices were calculated for all accessions using yield data in the driest (2019) and more favorable (2017) year. The total score of ranks for all indices was calculated for each accession. The total score correlated most strongly with the yield in an unfavorable year. As a result, 20 cultivars with the best total scores were identified, including 11 accessions bred in Aktobe Region, the reference cultivar, and promising accessions from other countries.Conclusion. The cultivars identified according to a set of indices are promising in terms of their use in breeding for drought resistance under the conditions of Aktobe Region. The proposed index system makes it possible to combine assessments of different drought tolerance aspects.